OpenCV 3.x with Python By Example : Make the most of OpenCV and Python to build applications for object recognition and augmented reality. - Joshi, Prateek (Packt Publishing, 2018)
Computer vision is found everywhere in modern technology. OpenCV for Python enables us to run computer vision algorithms in real time. With the advent of powerful machines, we have more processing power to work with. Using this technology, we can seamlessly integrate our computer vision applications into the cloud. Focusing on OpenCV 3.x and ...